2016
DOI: 10.1007/s10096-016-2597-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of statins on the outcome of Clostridium difficile infection in hospitalized patients

Abstract: • Clostridium difficile is the most common cause of infectious nosocomial diarrhea among hospitalized adult patients in the developed countries. • There is an increasing morbidity and mortality of CDI patients due to the emergence of new strains of high virulence. • Recent studies demonstrated that prior statin use has protective and ameliorating effects on morbidity and mortality among CDI patients. • Our study showed that concomitant statin use has no significant impact on short-term mortality, CDI severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…91,92 A small study of patients with CDI did not find a difference in mortality, severity, or complication of CDI in statin users as compared with nonusers. 93 Proposed mechanisms for statins to protect against CDI relate to the disruption of cholesterol production. Because statins interfere with cholesterol production at the beginning of the synthesis pathway, many downstream cholesterol-independent, pleotropic effects on inflammatory, and immunomodulation pathways have been observed and studied.…”
Section: Statinsmentioning
confidence: 99%
“…91,92 A small study of patients with CDI did not find a difference in mortality, severity, or complication of CDI in statin users as compared with nonusers. 93 Proposed mechanisms for statins to protect against CDI relate to the disruption of cholesterol production. Because statins interfere with cholesterol production at the beginning of the synthesis pathway, many downstream cholesterol-independent, pleotropic effects on inflammatory, and immunomodulation pathways have been observed and studied.…”
Section: Statinsmentioning
confidence: 99%
“…Two additional studies evaluated the association of statins with risk of 30-day CDI mortality. 32 , 33 Meta-analysis of these 2 studies also revealed a nonsignificant result (unadjusted OR, 0.91; 95% CI, 0.34–2.39; P =0.84) ( Figure 7B ).…”
Section: Resultsmentioning
confidence: 91%
“…Lastly, a retrospective study of 178 statin users and 321 statin non-users also saw a benefit in statin use in terms of 30-day mortality, as their multivariate analysis found that statin users were more likely to survive than non-users (OR 1.54), though the results were not significant (95% CI 0.850–2.789, p = 0.392). [20, 21]…”
Section: Discussionmentioning
confidence: 99%